Acute Presentation of Autoimmune Hepatitis: Case Report - Ghosh, Jaya; Ghosh , Jhumur (Journal for Research in Applied Sciences and Biotechnology, 2024)
This case report describes the clinical presentation, diagnostic evaluation, and treatment outcome of a 38-year-old female patient presenting with yellow discoloration of eyes and urine, along with associated symptoms such as nausea, poor appetite, abdominal pain, extreme fatigue, and mild joint pain. The patient had a history of amenorrhea for three months and no family history of autoimmune disease or drug-induced liver injury. Upon examination, the patient exhibited deep icterus and mild tender hepatomegaly, but without signs of acute liver failure. Laboratory investigations revealed elevated liver function markers and positive autoimmune antibodies, including antinuclear antibody (ANA) and anti-smooth muscle antibody (ASMA), while ruling out other possible etiologies such as viral hepatitis, Wilson's disease, and hemochromatosis. Imaging studies showed features of acute hepatitis, and liver biopsy could not be performed due to prolonged prothrombin time. The patient was diagnosed with probable autoimmune hepatitis (AIH) and initiated on a treatment regimen consisting of prednisolone 40 mg daily, which was gradually tapered over time and added azathioprine 100 mg daily. The patient demonstrated significant improvement in liver function tests with this treatment approach. However, she discontinued treatment on her own accord but continued to have normal liver function during subsequent follow-up visits. During the consultation, the patient and healthcare provider engaged in a comprehensive discussion concerning the significance of sustained treatment over an extended period and the inherent possibility of relapse.